How to Measure Tenatsˊ Satisfaction in Science and Technology Parks? A Case Study of Office Rental Services in Polish STP - Staszków , Michał (Studia Oeconomica Posnaniensia, 2016)
Creativity and the capacity to implement innovative solutions is widely acknowledged as a competitive advantage for businesses, cities or even regions. Theoretically the role of science and technology parks (STP) should be pivotal in establishing such an advantage. One of the main services provided by STPs, which allows them to fulfil their goals, is rental of office spaces. Competition in office rental services grew in the biggest cities in Poland; therefore an important issue becomes the quality of the services provided and the satisfaction of STPs’ customers. High quality office space can be certified according to the ISO 9001 standard, to obtain which it is necessary to carry out customer satisfaction surveys. The use of a Customer Satisfaction Index (CSI) allows the specification of customers’ needs and their satisfaction with services provided or products purchased. The author presents the concept of CSI and shows the practical application of it using the example of office space rental services provided by one of the Polish technology parks.